Kids make their own robots: good practices from the eCraft2Learn project - Dimitris Alimisis; Rene Alimisi; Dimitrios Loukatos; Emmanouil Zoulias (Firenze University Press, 2019)
This paper focuses on the small-scale pilots with learners that were carried out in Greece in the frame of the eCraft2Learn project including activities that aim at reinforcing learning by making in STEAM education. In the context of the pilots, 13-17 years-old students worked with digital fabrication and making technologies for creating robotic artefacts. In the framework of an appropriate pedagogical model that supports different steps highly interlinked, the teachers and students were invited to work together and explore the fun and the challenges of the making process using the eCraft2Learn learning ecosystem. In this line, a number of good practices were identified related to the facilitation of the learning process, the support of the ideation, the boosting of the can-do attitude, the embracement of failure and the encouragement towards sharing projects, experiences and ideas. Most of these practices are reflected in video-recorded episodes accessible through this paper.   I bambini creano i propri robot: buone pratiche dal progetto eCraft2Learn Il presente lavoro documenta le prime applicazioni realizzate in Grecia, nell'ambito del progetto eCraft2Learn, dedicato a rafforzare la formazione nell'area STEAM con il learning by making. Studenti tra i 13 e i 17 anni hanno applicato tecnologie digitali e tecniche artigianali per creare artefatti robotici. Nell'ambito di un modello pedagogico appropriato, in grado di supportare diversi passi altamente interconnessi tra loro, i docenti e gli studenti sono stati invitati a lavorare insieme e ad esplorare gli aspetti di divertimento e di sfida relativi al processo creativo utilizzando l'ecosistema di apprendimento eCraft2Learn. Nel progetto sono state identificate una serie di buone pratiche relative alla facilitazione del processo di apprendimento, al supporto all'ideazione, al rinforzo di un atteggiamento positivo, all'accettazione del fallimento e all'incentivazione della condivisione di progetti, esperienze, idee. La maggior parte di queste pratiche sono state video registrate e sono rese accessibili attraverso il presente articolo.